POLA MANAJEMEN DISTRIBUSI KOMPETENSI HOTS DALAM PEMBELAJARAN AKIDAH AKHLAK (Analisis KMA No. 165 TAHUN 2014) - Ahmad Dwi Khalim (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
The challenges of education are increasingly complex. The latest challenge about 21st century learning. Tuntutan wacana ini diataranya critical thinking. So learning the Higher Order Thinking Skill (HOTS) is important. This study aims to look at the pattern of distribution of basic competencies in the HOTS domain in KMA Number 165 of 2014 concerning the 2013 curriculum of PAI and Arabic subjects in Madrasah. This research is literature. The method of analyzing data using descriptive methods, the data obtained by documentation techniques. To focus the research, researchers used content analysis. To focus the research, researchers used the results of the study to show that Basic Competence (KD) was dominated by the level of understanding (C2), then remembering (C1) and applying (C3). While the HOTS level analyzing(C4) as the initial level of HOTS is still small compared to C2, C1, and C3. the level of analyzing (C4) is only 22 KD. As for evaluating (C5) and creating (C6) not yet. The pattern of distribution at the higher levels is more and more basic competencies in the HOTS domain. Or vice versa the lower the level the less basic competence of the HOTS domain.